2018
DOI: 10.1016/j.clnesp.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Topical vitamin D3: A randomized controlled trial (RCT)

Abstract: The results of this study indicate that transdermal route of vitamin D is potentially, safe and can give desired results to raise the vitamin D levels. This route is an alternate route for supplementation of vitamin D which should be utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…The protective effects of natural compounds show a significant impact on skin in various treatment regimen including pre- and post-treatment [94]. The post-treatment regimen has been used for vitamin D 3 treatment with some diseases including skin protection [95,96]. During the post-treatment, vitamin D 3 reduced the apoptosis and healing process in psoriasis [95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effects of natural compounds show a significant impact on skin in various treatment regimen including pre- and post-treatment [94]. The post-treatment regimen has been used for vitamin D 3 treatment with some diseases including skin protection [95,96]. During the post-treatment, vitamin D 3 reduced the apoptosis and healing process in psoriasis [95].…”
Section: Discussionmentioning
confidence: 99%
“…During the post-treatment, vitamin D 3 reduced the apoptosis and healing process in psoriasis [95]. Additionally, the post-treatment with topical vitamin D 3 has been used in clinical trial as well [96]. Therefore, we found that it is important to test the effect of compounds in protection against UV-induced skin damage when used in both pre-treatment and post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of natural compounds show a significant impact on skin in various treatment regimen including pre-and posttreatment [94]. The post-treatment regimen has been used for vitamin D 3 treatment with some diseases including skin protection [95,96].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from oral intake, vitamin D can also be administered intramuscularly with a similar, yet delayed, increase compared to oral intakes (134, 135, 136). Transdermal applications of vitamin D do also raise serum 25(OH)D, but more data on this topic are needed (137, 138). Apart from vitamin D, there are also 25(OH)D preparations available for treatment that are about 3.2–5-fold as effective as vitamin D in raising serum 25(OH)D concentrations (139, 140).…”
Section: Practical Vitamin D Testing and Supplementationmentioning
confidence: 99%